Physiological characterization of osmotolerant yeast Pichia sorbitophila and comparison with a putative synonym Pichia farinosa - Maresová, L; Sychrová, H (Folia microbiologica, 2003)
The osmotolerant yeast Pichia sorbitophila was found to differ from other yeast species, not only from the conventional ones (Saccharomyces cerevisiae, Schizosaccharomyces pombe), but also from those widely known as osmotolerant (Debaryomyces hansenii, Zygosaccharomyces rouxii). P. sorbitophila was able to survive extremely high extracellular concentrations of salts (e.g., saturated solution of KCl) and other osmolytes (70% glucitol), although it is not classified as halophilic (or osmophilic). P. sorbitophila assimilated a broad range of carbon and nitrogen sources with extreme effectiveness. On solid media, P. sorbitophila created colonies of variable shapes and sizes in relation to media composition, number of colonies on the plate and cultivation conditions. Colonies were able to produce long-distance signals between each other that resulted in growth inhibition of the facing parts of both colonies, but were not inhibited by colonies of other yeast species growing on the same plate. Though sometimes P. sorbitophila has been indicated as a synonym of P. farinosa, comparative physiological studies together with PCR amplification of P. farinosa DNA fragments homologous to known P. sorbitophila genes provided a strong indication that this strain should be classified as a separate species.
Keywords: DNA fungální; DNA, Fungal; Nitrogen; dusík; Chlorides; chloridy; Pichia; Osmotic Pressure; Schizosaccharomyces; Culture Media; osmolární koncentrace; kultivační média; Carbon; osmotický tlak; polymerázová řetězová reakce; Polymerase Chain Reaction; Saccharomyces cerevisiae; Zygosaccharomyces; uhlík; Osmolar Concentration